Use of Noninvasive Ventilation with Volume-Assured Pressure Support to Avoid Tracheostomy in Severe Obstructive Sleep Apnea - Montserrat Diaz-Abad; Amal Isaiah; Valerie E Rogers; Kevin D. Pereira; Anayansi Lasso-Pirot (Hindawi Limited, 2018)
Obstructive sleep apnea (OSA) is a common disorder in children but can occasionally present with life-threatening hypoxemia. Obesity is a significant risk factor for poor outcomes of OSA treatment. Continuous positive airway pressure (CPAP) is indicated in children who are not candidates for or have an unsatisfactory response to adenotonsillectomy. Children acutely at risk for significant morbidity with other therapies are candidates for a tracheostomy. An eight-year-old patient with morbid obesity and severe OSA refractory to CPAP therapy was treated successfully with a novel noninvasive ventilation (NIV) mode with volume-assured pressure support (VAPS) and avoided tracheostomy.